Experimental Investigation of 5G Positioning Performance Using a mmWave Measurement Setup - Yammine, George; Alawieh, Mohammad; Ilin, Gregor; Momani, Mohammad; Elkhouly, Mostafa; Karbownik, Piotr; Franke, Norbert; Eberlein, Ernst (2021 International Conference on Indoor Positioning and Indoor Navigation (IPIN), 2021)
Driven by an ever-increasing demand for higher data rates, 5G introduced communication over the millimeter-wave (mmWave) bands to fulfill this requirement. High data transmissions in this spectrum are enabled by beamforming massive MIMO antennas and the available allocated bandwidth. Of interest is the utilization of mmWave for high-accuracy positioning applications, motivated by the allocated bandwidth and beamforming characteristics of such systems. This paper provides numerical simulations on the 5G positioning reference signal reception and shows, for a real-world indoor environment, positioning performance results. The accuracy of ToA-based positioning in dependence of the beam shape and direction is determined to be at least within 6cm for LOS scenarios. We also investigate the impact of LOS path obstructions on the performance. Achieving centimeter level accuracy is subject to improvements through continuing research and refinements.